Uncovering the Link Between Servant Leadership and Loyalty: a Prisma-Based Systematic Review - Rosul, Ahmad; Fathiyah, Kartika Nur; Fitri, Aroviani Amsa; Kiat, Ton (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2025)
In the context of modern organizations, leadership and employee loyalty are interrelated factors that significantly impact optimal performance. This systematic review examines the relationship between servant leadership (SL) and employee loyalty, highlighting how SL prioritizes employee well-being compared to traditional power-oriented leadership models. The study identifies that effective servant leadership fosters a supportive environment, enhances individual growth, and ultimately contributes to improved organizational performance. Employee loyalty, characterized by commitment and emotional attachment to the organization, plays a crucial role in maintaining stability and efficiency within the company. This review synthesizes existing literature to explore how servant leadership can concretely influence employee loyalty through mechanisms such as empowerment and job satisfaction. The findings suggest that while employee satisfaction serves as a mediator in this relationship, other factors also play significant roles. This research aims to provide deeper insights into how servant leadership can cultivate stronger loyalty in the workplace, thereby enhancing overall organizational performance.